Perspectives on branding - Miletsky, Jason I.; Smith, Genevieve (Boston, Mass. : Course Learning, 2009)
Who$1 (Bs the real branding expert: the agency or the brand? Each has a different approach to what brand building's really all about and the methods needed to generate consumer loyalty. Each approaches brand building strategies from a different angle - a different perspective - and without understanding both points of view, the picture is never fully complete. Perspectives on Branding is the first book to offer both sides of the story. In an easy-to-read, question/answer format, Jason Miletsky provides the agency perspective while Genevieve Smith gives the brand point of view on topics including what a brand actually is (not many people really get it, operationalizing the brand and making it tangible, successfully marketing the brand, the best ways to measure results, which brands do it right, and which brands do it wrong and a whole lot more. What makes this book different from other branding books is that there is no author collaboration or sharing of information during the writing process. Neither author was aware of what the other was writing. The result is a fascinating, no-holds-barred look at branding as both the client and brand see it, leaving readers with a list of action items and a better understanding of core brand building concepts to dramatically improve their strategies.s
Part One: Understanding the Brand -- Part Two: Operationalizing the Brand -- Part Three: Marketing the Brand -- Part Four: Brand Evaluation and Evolution -- Part Five: Just for Fun.
Includes index.
APPSCIE, NBK
1
Keywords: Branding (Marketing); Brand name products; Branding (Marketing) -- Case studies; Brand name products -- Case studies